Clinical Features and Treatment in the Spectrum of Paroxysmal Dyskinesias: An Observational Study in South-West Castilla y Leon, Spain. (2nd May 2019) - Manso-Calderón, Raquel
Abstract : Background . Paroxysmal dyskinesias (PxD) are a group of heterogeneous disorders characterized by intermittent episodes of involuntary movements. PxD include paroxysmal kinesigenic (PKD), nonkinesigenic (PNK), and exercise-induced (PED) varieties. Objectives . To define the phenotype of primary and secondary PxD forms. Methods . Twenty-two patients with PxD (9 men/13 women) were evaluated in two hospitals in south-west Castilla y Leon, Spain. Clinical features of the episodes, causes, family history, and response to treatment were collected. Results . Thirteen participants with primary PxD (6 men/7 women) and 9 with secondary PxD (3 men/6 women) were recruited. Nine patients belong to three nonrelated families (2 had PKD and 1 had PED). Mean age at onset in primary PKD cases was 10 years (range 5-23 years), earlier than in PNKD (24 years) and PED (20 years). Most primary PKD cases experienced daily episodes of duration <1 minute, which are more frequent and shorter attacks than in PNKD (1-2 per month, 5 minutes) and PED (1 per day, 15 minutes). The location of the involuntary movements varied widely; isolated dystonia was more common than mixed chorea and dystonia. All PKD patients who received antiepileptic treatment significantly improved. Levodopa and ketogenic diet proved to be effective in two patients with PED. Secondary forms presented a later mean age of onset (51 years). Six cases had PNKD, 1 had PKD, 1 both PNKD and PKD, and 1 had PED. Causes comprised vascular lesions, encephalitis, multiple sclerosis, peripheral trauma, endocrinopathies, and drugs such as selective serotonin reuptake inhibitors (SSRIs). Conclusion . The knowledge of the clinical features and spectrum of causes related to PxD is crucial to avoid delays in diagnosis and treatment, or even a nonorganic disorder diagnosis.